Towards benchmarking VR sickness: A novel methodological framework for assessing contributing factors and mitigation strategies through rapid VR sickness induction and recovery - Rouhani, Rose; Umatheva, Narmada; Brockerhoff, Jannik; Keshavarz, Behrang; Kruijff, Ernst; Gugenheimer, Jan; Riecke, Bernhard E. (Displays, 2024)
Virtual Reality (VR) sickness remains a significant challenge in the widespread adoption of VR technologies. The absence of a standardized benchmark system hinders progress in understanding and effectively countering VR sickness. This paper proposes an initial step towards a benchmark system, utilizing a novel methodological framework to serve as a common platform for evaluating contributing VR sickness factors and mitigation strategies. Our benchmark, grounded in established theories and leveraging existing research, features both small and large environments. In two research studies, we validated our system by demonstrating its capability to (1) quickly, reliably, and controllably induce VR sickness in both environments, followed by a rapid decline post-stimulus, facilitating cost and time-effective within-subject studies and increased statistical power, (2) integrate and evaluate established VR sickness mitigation methods — static and dynamic field of view reduction, blur, and virtual nose — demonstrating their effectiveness in reducing symptoms in the benchmark and their direct comparison within a standardized setting. Our proposed benchmark also enables broader, more comparative research into different technical, setup, and participant variables influencing VR sickness and overall user experience, ultimately paving the way for building a comprehensive database to identify the most effective strategies for specific VR applications.
Keywords: Benchmark system; FOV reduction; Motion sickness; NSERC DG 2026; Riecke; Riecke_2024; VR sickness; Virtual nose; Virtual reality; behrang-keshavarz; bernhard-riecke; ernst-kruijff; jan-gugenheimer; jannik-brockerhoff; journalPaper; narmada-umatheva; proj--; proj--VR-sickness-benchmark; rose-rouhani